Portaria PRRJ nº 96, de 31 de janeiro de 2023 - Sergio Luiz Pinel Dias (DMPF-e, Brasília, DF, 2 fev. 2023 . Caderno Extrajudicial, p. 28., 2023)
DMPF-e, Brasília, DF, 2 fev. 2023 . Caderno Extrajudicial, p. 28.